1989
DOI: 10.1210/jcem-69-5-1033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Circulating Inhibin Levels during the Luteal-Follicular Transition of the Human Menstrual Cycle *

Abstract: Dynamic changes in serum immunoreactive (ir) inhibin levels during the transition from the luteal to the follicular phase (luteal-follicular transition) were characterized during 3 consecutive cycles in 12 cycling women. Both spontaneous (first to second cycle) and GnRH antagonist-imposed premature luteolysis (second to third cycle) were evaluated. Serum FSH, LH, estradiol (E2), and progesterone (P4) levels were monitored daily by RIA for the entire study. Daily ir-inhibit levels were determined from 7 days be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
8

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 0 publications
2
51
0
8
Order By: Relevance
“…In addition, Fraser et al [23] reported that anti-inhibin serum administration to the stump-tailed macaque in the mid-luteal phase did not have significant effects on serum FSH, but they found a significant increase in serum FSH in the early follicular phase of the following cycle. The report of Fraser et al also indicates that inhibin is not the sole factor in suppressing FSH secretion during the luteal phase [24] but probably plays an important role in the selective inhibition of FSH release, particularly in the luteal-follicular transition phase where circulating progesterone and E2 are quite low [5]. Because PCOD patients have no cycles and their pituitary gland is chronically exposed to slightly increased inhibin, it is likely that inhibin is involved in modulating FSH secretion in women with PCOD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Fraser et al [23] reported that anti-inhibin serum administration to the stump-tailed macaque in the mid-luteal phase did not have significant effects on serum FSH, but they found a significant increase in serum FSH in the early follicular phase of the following cycle. The report of Fraser et al also indicates that inhibin is not the sole factor in suppressing FSH secretion during the luteal phase [24] but probably plays an important role in the selective inhibition of FSH release, particularly in the luteal-follicular transition phase where circulating progesterone and E2 are quite low [5]. Because PCOD patients have no cycles and their pituitary gland is chronically exposed to slightly increased inhibin, it is likely that inhibin is involved in modulating FSH secretion in women with PCOD.…”
Section: Discussionmentioning
confidence: 99%
“…We collected control samples on days 2 to 5 from the onset of menstruation because it had been found that the lowest inhibin levels are detected on day 2 after the onset of menstruation [5], while Buckler et al, collected control samples on days -9 to -7 based on the midcycle gonadotropin surge. Our results indicate that serum IR-inhibin levels in PCOD women are significantly higher than those in normal women in the early stage of the menstrual cycle, but it still remained nuclear whether the inhibin concentration detected in PCOD plays a significant role in selective inhibition of FSH secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both estradiol and inhibin are longknown potent suppressors of FSH secretion, leading to a progressive decline of FSH secretion during the mid to late follicular phase. In contrast, corresponding circulating LH levels exhibit a progressive increasing trend, ultimately leading to ovulation (4).…”
Section: Discussionmentioning
confidence: 95%
“…This applies particularly to females, whose preference for symmetry could vary across the menstrual cycle such that it will be lower during the low-fertility (menstrual and luteal) phases, when luteinizing hormone is low, and higher during the high-fertility (ovulatory) latefollicular phase, when luteinizing hormone is high (e.g., Roseff et al, 1989). Normally, fertility (the probability of conception) is high between Days 10 and 17 of the cycle, and highest 2 days prior to ovulation, but drops substantially 1 day after ovulation (Dunson, Baird, Wilcox, & Weinberg, 1999).…”
Section: The Role Of Symmetrymentioning
confidence: 99%